Ridge-furrow with plastic film and straw mulch increases water availability and wheat production on the Loess Plateau - Liu, Gaoyuan (Sci Rep, 2018)
Mulching is critical for increasing water availability and hence winter wheat production in dryland farming systems. A two-year study was conducted to assess the effects of mulches on soil water storage (SWS), temperature, water use efficiency (WUE) and yields of winter wheat on the Loess Plateau. Four treatments were examined: conventional flat planting (CK), straw mulch (FPS), transparent plastic film mulch (FPP) and ridge-furrow with plastic film-mulched ridge and straw-mulched furrow (RFPS). Compared with CK, RFPS greatly increased SWS from 0–60 cm, FPP increased SWS from 0–40 cm, and FPS slightly increased SWS from 0–60 cm; however, FPP significantly (P < 0.05) decreased SWS from 61–100 cm. RFPS and FPP increased soil temperatures in cold seasons relative to CK, especially in RFPS (2.0–2.3 °C). Meanwhile, the rate of soil temperature increase was greater in RFPS and FPP than in CK but was lower in FPS. Mean yields were significantly increased in RFPS (56.78%), FPP (44.72%) and FPS (9.57%), and WUE was significantly increased in RFPS (44.04%) and in FPP (37.50%) compared with CK (P < 0.05). We conclude that ridge-furrow planting with plastic film-mulched ridge and straw-mulched furrow has a good potential for raising winter wheat production on the Loess Plateau.